Implementasi Dynamic Governance Program Kampung Tematik Tangerang: Studi Kasus Kampung Jimpitan - Silawarti, Rifdah; Hilman, Hilman; Yus Firdaus, Muhammad (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
This research aims to understand the principles, challenges, and impacts of dynamic governance implementation on program sustainability. We used a descriptive qualitative method with a post-positivist paradigm. Data was collected through interviews, observation, and documentation from stakeholders, including the government, LPM, PKK, RT, and RW. Analyzed using the Miles and Huberman model and source triangulation. The results show Kampung Jimpitan's success in integrating visionary planning (Thinking Ahead) for long-term development, continuous evaluation and adaptation (Thinking Again) based on citizen input, and cross-sector collaboration (Thinking Across) with government, private entities, and inter-village comparative studies. Program implementation faces challenges including bureaucracy, fluctuations in community participation, and budget and time constraints. This implementation has an impact on improving community welfare through food security and economic empowerment, strengthening inclusive community leadership, and positioning Jimpitan Village as an inspiration for other thematic villages in realizing positive sustainable change.